Experiences of professional nurses in providing support to student nurses in the clinical practice environment of a private hospital in Gauteng - Jones, Jennifer (My University, 2021)
Quality in nursing education is a global focus due to the many challenges facing healthcare the world over. Clinical learning is an important component in nursing training and nursing experiences during clinical placement are crucial to prepare the student to become safe, competent Professional Nurses. However recent studies have shown that the students’ clinical training is not always effective in preparing them for their future role. Support in the clinical environment by the Professional Nurse is crucial to assist the student to develop confidence and competence to transition into the Professional Nurse role. The objective of this study was to describe the experiences of Professional Nurses in providing support to student nurses in the clinical practice environment of a private hospital. An exploratory qualitative study using in depth interviews of fifteen Professional Nurses was done. The data collected was then analysed using thematic analysis. The identified themes and categories were discussed to offer meaning and insight. The study provided an understanding of how support of the student nurse is currently experienced and perceived by the Professional Nurse in the clinical practice environment with a view to identifying ways of improving support to the student nurse in the future. It was found that the clinical environment is unpredictable and whilst the Professional Nurses acknowledged they needed to support the student, it was often challenging to do this effectively leaving them feeling frustrated and disappointed. The study took place during the COVID -19 pandemic which caused major disruptions to the everyday functioning and operations of hospitals globally, and the study site was no exception. Recommendations to improve support to the student nurse were made in the areas of Clinical Practice, Nursing Education and Research.
A research report submitted in fulfilment of the requirements for the degree Master of Science in Nursing to the Faculty of Health Sciences, School of Nursing, University of the Witwatersrand, Johannesburg, 2021
Keywords: SDG-4: Quality education